Δλ-Statistical boundedness on time scales. Issue 3 (1st February 2021) - Altin, Yavuz; Er, Büşra Nur; Yilmaz, Emrah
Abstract: In this study, we examine the notion of Δ λ -statistical boundedness on an arbitrary time scale. Moreover, some inclusion relations are obtained.